PENGARUH PEMAHAMAN FIQH MUAMALAH MAHASISWA TERHADAP KEPUTUSAN PEMBELIAN PRODUK DENGAN MEREK DAGANG TIRUAN - Ahmad, Sofia (Aksara Public, 2019)
This study aims to determine the level of understanding of muamalah fiqh on imitation trademarks, knowing the use of products with imitation trademarks on and to know the effect of understanding muamalah fiqh on 5th and 7th semester students (class 2016-2017) Islamic Economics Study Program at Ibn Khaldun University Bogor on purchasing decisions products with imitation trademarks. This study uses a quantitative approach. Quantitative approach is carried out by recording and analyzing the data of research results carried out using statistical calculations. The population in this study were students in the 5th and 7th semester (2016-2017) of the Sharia Economics study program at the University of Ibn Khaldun, Bogor. This study uses a Non-Probability sampling technique by purposive sampling. This study shows that students in the 5th and 7th semester (2016-2017) of the Sharia Economics Study Program at Ibn Khaldun University, Bogor, although they have understood the understanding of Muqalat Fiqh, but still make imitation brand purchases on the grounds that imitation brand items have a much cheaper price with original brand and has a similar model, so students prefer and decide on the purchase of goods that have an imitation brand. And according to the results of t-test data processing, it is known that the calculated t value of the Muamalat Fiqh Understanding variable is 0,000. Because the value of 14,888> 1,656 and the coefficient value of Muamalat's Fiqh Understanding variable is positive, it is concluded that there is a positive and significant influence between Muamalat's Fiqh Understanding with Decision of Buying Products with Artificial Brand Statistically